Decision confidence in the Ellsberg experiment - Peter Duersch (University of Heidelberg, Department of Economics, 2015)
Subjects are asked to report their confidence in their own decisions regarding the Ellsberg three color urn. Subjective confidence is measured via a 5 point Likert scale. Surprisingly, subjects are more confident in their answer for the more complicated two color question, compared to the simple one color question. This is robust across a wide range of experimental contexts.
urn:nbn:de:bsz:16-heidok-188377
Keywords: 330; Ellsberg experiment; Confidence